Systematic pharmacology-based strategy to investigate the mechanism of beta-sitosterol for the treatment of rheumarthritis - Wang, Xiaodong; Mao, Jingxin (Frontiers in Genetics, 2024)
Objective: β-Sitosterol, which is derived from Vladimiriae Radix (VR), is used for the treatment of rheumatoid arthritis (RA), but the pharmacological mechanisms through which β-sitosterol affects RA have not been fully elucidated.Methods: Through the Traditional Chinese Medicine Systems Pharmacology and Analysis (TCMSP), PubChem, SwissTargetPrediction, GeneCards, DisGeNET, and OMIM databases, “β-sitosterol-RA”-related genes were obtained, and a target protein interaction network (protein–protein interaction [PPI]) was constructed. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were carried out for the intersecting genes. Discovery Studio 2019 software was used to perform molecular docking on MMP9, CASP3, HSP90AA1, SRC, EGFR, and ALB genes. β-Sitosterol was co-cultured with MH7A cells in three experimental groups: control group (DMSO), positive drug group (methotrexate, 80 μmol/L), and drug intervention group (10, 20, 40, 80, and 160 μmol/L β-sitosterol). The CCK8 method was used to investigate the inhibitory effect of β-sitosterol on the proliferation of MH7A cells. RT-PCR was used to analyze the mRNA expression of the abovementioned core targets.Results: A total of 41 genes associated with β-sitosterol and RA were obtained, mainly involving the FoxO signaling pathway and PI3K/AKT signaling pathway. The molecular docking results suggested that β-sitosterol could bind effectively to six core targets. The experimental results showed that β-sitosterol could significantly inhibit the excessive proliferation of MH7A cells (p< 0.05). The RT-PCR results showed that the expression of MMP9, HSP90AA1, SRC, EGFR, and ALB core genes in the control group was significantly upregulated, while the CASP3 gene was downregulated. Compared to the control group, the mRNA expression of MMP9, HSP90AA1, SRC, EGFR, and ALB decreased (p< 0.01), while the apoptosis-related gene CASP3 increased in both the drug intervention (80 μmol/L β-sitosterol) and positive drug groups (80 μmol/L methotrexate).Conclusion: Hence, β-sitosterol could contribute to the inhibition of RA by modulating cell proliferation and regulating the aforementioned six core proteins, potentially through the regulation of the FoxO and PI3K/AKT signaling pathways.